2018
DOI: 10.1038/s41419-018-1032-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of SUN2 by DNA methylation is associated with HSCs activation and hepatic fibrosis

Abstract: Hepatic myofibroblasts, activated hepatic stellate cells (HSCs), are the main cell type of extracellular matrix (ECM) deposition during hepatic fibrosis. Aberrant DNA methylation-regulated HSCs activation in liver fibrogenesis has been reported, but the functional roles and mechanisms of DNA methylation in hepatic fibrosis remain to be elucidated. In the present study, reduced representation bisulfite sequencing (RRBS) analysis of primary HSCs revealed hypermethylation patterns in hepatic fibrosis. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In EBi3 -/mice, infection caused an increase in DNA demethylation and analyzing EBi3 -/-C versus EBi3 -/-I we can see that TET1 plays the major differences observed in S2, but TET2 and TET3 also increased strongly their expression values. The literature lacks data about methylation and demethylation of DNA in hepatic tissues during schistosomiasis, but considering other disease that affect the liver causing collagen deposition, there is an increase in liver methylation during hepatic fibrosis development, as determined by analyzing the overall methylation and the methylation of specific genes (Septina9, Long non-coding RNA H19, SUN2) in diseases such as hepatocarcinoma, hepatitis and cirrhosis [10,11,28], this occurred in our control groups WTC and WTI considering the qRT-PCR data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In EBi3 -/mice, infection caused an increase in DNA demethylation and analyzing EBi3 -/-C versus EBi3 -/-I we can see that TET1 plays the major differences observed in S2, but TET2 and TET3 also increased strongly their expression values. The literature lacks data about methylation and demethylation of DNA in hepatic tissues during schistosomiasis, but considering other disease that affect the liver causing collagen deposition, there is an increase in liver methylation during hepatic fibrosis development, as determined by analyzing the overall methylation and the methylation of specific genes (Septina9, Long non-coding RNA H19, SUN2) in diseases such as hepatocarcinoma, hepatitis and cirrhosis [10,11,28], this occurred in our control groups WTC and WTI considering the qRT-PCR data.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are fundamental for gene expression regulation, sex X chromosome silencing in females, transposon silencing [8,9]. Diseases that affect the liver causing collagen deposition induct alterations in the expression of DNA methyltransferases and DNA demethylases, leading to disturbance in expression of several genes [10,11], here we intended evaluate in schistosomiasis. DNMT1 enzyme is related to the maintenance of existing methylation during the replication process, copying the patterns from the template to the new strand, and is more expressed in the period before mitosis.…”
mentioning
confidence: 99%
“…It has been shown that 5-azadC, an inhibitor of DNA methyltransferase, can block the enzymatic activity of all three methyltransferases 32. We have previously demonstrated that 5-azadC could reduce liver injury and inhibit the expression of COL1a1 and α-SMA in primary HSCs 33. To investigate whether the down-regulated expression of RCAN1.4 in activated HSCs was attributed to DNA methylation, 5-azadC 34 and DNMTs-RNAi were employed.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the genome of an organism, the epigenome is not a consistent entity and may be modulated by different intrinsic, chemical, and environmental cues [87], and its changes may be inherited across generations [88]. DNA methyltransferases (DNMTs), such as DNMT1, DNMT3a, and DNMT3b, enable DNA methylation, which is correlated with the conversion of quiescent HSC into hepatic myofibroblasts [89]. DNA methylation inhibitors exert a regulatory effect on hepatic wound healing and fibrogenesis [90,91].…”
Section: Mir-29a Functions As An Epigenetic Modifier To Mitigate Livementioning
confidence: 99%